The inverse correlation between serum zinc levels and depression severity in Egyptian adolescent students: a case–control study - Amany H. Abdelmoneam; Ghada M. Khafagy; Khaled A. Elbeh; Marwa D. A. Hasan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Depression significantly impacts adolescents’ quality of life, with zinc deficiency suggested as a contributing factor. This study aimed to explore the relationship between serum zinc levels and depression among Egyptian adolescent students, hypothesizing an inverse correlation between zinc levels and depression severity. In a case–control study, 358 students from two randomly selected secondary schools in (blind to peer review) Governorate, Egypt, were screened for depression using the Arabic version of the Beck Depression Inventory. Based on the screening, 86 cases with depression and 86 matched controls were identified. Serum zinc levels were measured, and socio-economic status (SES) was assessed using the Gilany SES questionnaire. Statistical analysis was conducted using SPSS 26.0, employing t-tests, ANOVA, and Chi-square tests, with significance set at p < 0.05. Results The study found a statistically significant difference in serum zinc levels between depressed and non-depressed groups, with depressed participants exhibiting lower zinc levels. Furthermore, a significant negative correlation was observed between depression severity and zinc levels, even after adjusting for age, sex, and SES. The predictive value of zinc levels in diagnosing depression demonstrated a sensitivity of 64% and specificity of 60.5%. Conclusions The findings confirm the hypothesis of an inverse relationship between serum zinc levels and depression among adolescents, underscoring the potential role of zinc in depression's pathophysiology and its relevance in preventive and therapeutic strategies. Future research should investigate the mechanisms underlying this association and evaluate zinc supplementation's efficacy in depression management.